Coronary heart disease alters intercellular communication by modifying microparticle‐mediated microRNA transport. Issue 21 (13th September 2013) - Finn, Nnenna A.; Eapen, Danny; Manocha, Pankaj; Al Kassem, Hatem; Lassegue, Bernard; Ghasemzadeh, Nima; Quyyumi, Arshed; Searles, Charles D.
Abstract : Coronary heart disease (CHD) is characterized by abnormal intercellular communication and circulating microRNAs (miRNAs) are likely involved in this process. Here, we show that CHD was associated with changes in the transport of circulating miRNA, particularly decreased miRNA enrichment in microparticles (MPs). Additionally, MPs from CHD patients were less efficient at transferring miRNA to cultured HUVECs, which correlated with their diminished capacity to bind developmental endothelial locus‐1 (Del‐1). In summary, CHD was associated with distinct changes in circulating miRNA transport and these changes may contribute to the abnormal intercellular communication that underlies CHD initiation and progression. Abstract : The circulating miRNA transport profile is altered in coronary heart disease (CHD) patients. CHD is associated with decreased miRNA loading of microparticles (MPs). CHD is associated with decreased transfer of miRNA from MPs to recipient cells. MPs isolated from CHD patients have diminished capacity to bind Del‐1.